Energy Decay for a Type of Plate Equation with Degenerate Energy Damping and Source Term (Journal of Partial Differential Equations, 2023)
In this paper, we mainly investigate the initial boundary value problem fora plate equation with non-local degenerate energy damping term and source term. Byusing potential well and Nakao’s inequality, we establish the global existence and theenergy decay rate when the initial data is starting in the stable set. Finally, we derivesome further estimate on the stability.
Keywords: Plate equation; global existence; energy damping; non-exponential decay.